ASUHAN KEPERAWATAN PEMENUHAN KEBUTUHAN AKTIFITAS PADA PASIEN LUKA BAKAR DENGAN INTERVENSI MANAJEMEN FISIOTERAPI DI RUANG ANGGREK C RSUD KABUPATEN TANGERANG - Ati Setiawati; Cicirosnita J.Idu; Ahmad Hambali (Nusantara Hasana Journal, 2024)
Burns continue to pose a challenge for health professionals and are also one of the most prevalent health issues in the world, resulting in a permanent impairment of function and appearance. The Tangerang District Hospital reported that the number of patients treated for burns was 8 in October 2023, 6 in November 2023, and 11 in December 2023, according to statistical data. Objective of this research to improve the patient's activity abilities by providing physical therapy interventions. Observations were carried out for 3 days after the patient was given physical therapy for 15-30 minutes on both limbs, hands and feet, both before and after using the MMT (Manual Muscle Testing) questionnaire which contains 7 statements, each of which has an assessment which is then added up. After giving physical therapy for 3 days, the results of the MMT questionnaire showed that the results on the first day were 25, on the second day they were 26, then on the third day they were 29. Utilizing the paired sample t-test, the sig value obtained. After conducting a two-tailed analysis, it is evident that physical therapy can enhance the patient's muscle activity and functionality.